(untitled) (Research, Society and Development, 2020)
The use of different didactic resources to develop specific themes in Science Education can work as a facilitator in what we call the teaching and learning process. This article proposes to bring, then, the use of a model as a didactic resource to work on a specific theme, being thought and developed for the early years of Elementary Education. In this context, the main objective of the research was to show the importance of using didactic materials such as models in an activity involving the theme of preventive care with the group of spiders, aiming at discussing and reflecting on this subject in Science Education and in the Initial Formation of pedagogues. The research was developed during the first semester of 2019, in a discipline entitled ‘Science Teaching in Early Childhood Education and Early Years of Elementary Education’, offered to students of the Pedagogy course. The data were collected through conversation circles and the use of a researcher’s Field Diary, both analyzed qualitatively. The use of a didactic model allowed the students to make better use of the content developed during the activity, in an open and problematizing way. In addition, the model used as a teaching resource can help future teachers to boost their classes, promoting a greater participation of children during the discussions and problems that will arise during the proposed activity.